TRI RISMAHARINI’S ANDROGYNOUS LEADERSHIP: STRATEGIZING “HEGEMONIC MASCULINITY”i - Kurniawati Hastuti Dewi Kurniawati Hastuti Dewi (Program Magister Ilmu Politik, Universitas Diponegoro, 2016)
This paper analyses the leadership style of Tri Rismaharini, the Mayor of Surabaya City (2010-2020) using feminist research methodology by centralizing on women‟s personal experiences in a specific context to gain knowledge based on their real life experiences. It employed a qualitative approach by using various videos and written materials of Risma‟s attitudes and experiences as a female political leader. The findings discover that unlike the common feminine leadership style of Indonesian female political leaders, Risma‟s shows a masculine leadership style. It can be seen from her assertive approaches while closing down Gang Dolly located in Surabaya as the biggest red-light district in Southeast Asia. Interestingly, Risma‟s masculinity is combined with motherly value which results in an androgynous leadership style. This paper shows that rather than merely accepting the western notion which believes that the more a woman shows masculinity, the more she hits the ground running for exercising power in the male-dominated political atmosphere. This paper would like to show that Javanese society‟s acceptance of Risma‟s leadership style indicates their approval for female leadership and wider tolerance towards new value of masculinity performed by a female leader despite inconsistency with the gender normative standard of feminine Javanese women. This paper concludes by emphasizing that Risma‟s masculine leadership traits can be seen as strategizing a move towards hijacking “hegemonic masculinity”.Keywords: leadership style, masculine, feminine, Javanese, androgynous.